The association of dietary phosphorus with blood pressure: Results from a secondary analysis of the PREMIER Trial - McClure, Scott T (J Hum Hypertens, 2019)
Inconsistent findings exist for the association between dietary phosphorus intake and blood pressure (BP). We examined the longitudinal association between urinary excretion and dietary intake of phosphorus (total, plant, animal, and added) with BP. This is a secondary analysis of PREMIER, a randomized behavioral intervention study in adults (25–79y) with BP, measured at six months, as the primary outcome. We classified total phosphorus intake from dietary recalls into plant, animal, and added phosphorus. We modeled six month change of phosphorus intake (from 24h dietary recalls, N = 622) and excretion (from 24h urine collection, N = 564) on BP, using linear regression crude and adjusted for intervention, age, race, sex, income, education, study site, and change in energy intake (kcal/d), sodium intake (mg/d), fitness (heart rate, bpm), and DASH diet index. Baseline phosphorus intake was 1154 mg/d (95%CI 1126, 1182) with 38%, 53%, and 10% from plant, animal, and added phosphorus, respectively. Total phosphorus intake was not associated with significant changes in BP. Increased urinary phosphorus excretion was associated with a significant increase in DBP [0.14 mmHg/100 mg (0.01, 0.28), adjusted]. In several analyses, phosphorus type (plant, animal, or added) significantly modified the association between phosphorus intake and BP. For example, added phosphorus (but not plant or animal) was associated with increases in SBP and DBP, 1.24 mmHg/100 mg (0.36, 2.12) and 0.83 mmHg/100 mg (0.22, 1.44), respectively, crude. These findings suggest that the type of phosphorus may modify the association between phosphorus intake and BP. Trial registration (clinicaltrials.gov).